The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0036-46652012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dams and irrigation schemes in Anopheline (Diptera: Culicidae) bionomics and malaria epidemiology

Abstract: SUMMARYIrrigation schemes and dams have posed a great concern on public health systems of several countries, mainly in the tropics. The focus of the present review is to elucidate the different ways how these human interventions may have an effect on population dynamics of anopheline mosquitoes and hence, how local malaria transmission patterns may be changed. We discuss different studies within the three main tropical and sub-tropical regions (namely Africa, Asia and the Pacific and the Americas). Factors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…In 2005, it was estimated that a total 3.1 million people were at risk of malaria due to dams in sub-Saharan Africa [24]. Sanchez et al [25] reported different patterns of malaria transmission in areas around large and small dams. Using a more extensive data set, Kibret et al [26] reported that more than 15 million people were at risk and that 1.1 million cases a year were associated with 1268 large dams in South-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, it was estimated that a total 3.1 million people were at risk of malaria due to dams in sub-Saharan Africa [24]. Sanchez et al [25] reported different patterns of malaria transmission in areas around large and small dams. Using a more extensive data set, Kibret et al [26] reported that more than 15 million people were at risk and that 1.1 million cases a year were associated with 1268 large dams in South-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Amazon deforestation and other perturbations in the forest landscape are fundamental consequences of the construction of hydroelectric dams, waterways and irrigation systems (Sanchez-Ribas et al 2012, Tundisi et al 2014, Fearnside 2015. A good example is the Belo Monte hydroelectric power plant, which significantly changed the landscape of the Xingu River in the Brazilian Amazon, flooding an area of 516 km 2 [228 km 2 (44%) corresponding to the original riverbed and seasonally flooded area] (ANA 2019).…”
Section: Hydroelectric Dams Waterways and Irrigation Systemsmentioning
confidence: 99%
“…The strongest effect of dam construction on the dynamics of infectious diseases concerns vector proliferation. Flooding of hitherto dry areas creates new breeding sites for disease vectors, especially mosquitoes, which contributes to the increase in the cases of various arboviral and parasitic infections (Sanchez-Ribas et al 2012, Fearnside 2015, Brito et al 2018.…”
Section: Hydroelectric Dams Waterways and Irrigation Systemsmentioning
confidence: 99%
“…Changes in downstream water quality have decimated the fisheries, waterfowl and mammals of the world's deltas, causing for example, by the year 2000 the endangerment or extinction for some 30% of the world's fresh water fish (WCD 2000). Damming and flood control have also resulted in increases in the frequency and severity of floods (WCD 2000), have played a role in inducing earthquakes (Qiu 2012), and have prompted increases in the transmission and prevalence of vector‐borne and parasitic diseases such as malaria and schistosomiasis (Sanchez‐Ribas et al 2012).…”
Section: Global Patterns Biocultural Consequencesmentioning
confidence: 99%